2005
DOI: 10.1289/ehp.7497
|View full text |Cite
|
Sign up to set email alerts
|

Inhalation Toxicity of Brevetoxin 3 in Rats Exposed for Twenty-Two Days

Abstract: Brevetoxins are potent neurotoxins produced by the marine dinoflagellate Karenia brevis. Exposure to brevetoxins may occur during a K. brevis red tide when the compounds become aerosolized by wind and surf. This study assessed possible adverse health effects associated with inhalation exposure to brevetoxin 3, one of the major brevetoxins produced by K. brevis and present in aerosols collected along beaches affected by red tide. Male F344 rats were exposed to brevetoxin 3 at 0, 37, and 237 μg/m3 by nose-only i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 24 publications
1
30
0
Order By: Relevance
“…It is possible that brevetoxin may impact proliferative responses of both T-and B-cell populations, but proliferative response following treatment with LPS or another B-cell mitogen was not investigated in this study. However, B-cell populations have been shown to be impacted by red tide toxin exposure in rodent models (Benson et al, 2005), so B-cell responses in rescued manatees will be a target in future studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that brevetoxin may impact proliferative responses of both T-and B-cell populations, but proliferative response following treatment with LPS or another B-cell mitogen was not investigated in this study. However, B-cell populations have been shown to be impacted by red tide toxin exposure in rodent models (Benson et al, 2005), so B-cell responses in rescued manatees will be a target in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Effects of red tide toxin exposure on immune function in sea life have been reported (Bossart et al, 1998;Walsh et al, 2005). Brevetoxins have been found within immune cells from a variety of species, including manatees (Bossart et al, 1998), cormorants (Kreuder et al, 2002), and following experimental exposure in laboratory animals (Benson et al, 1999(Benson et al, , 2004(Benson et al, , 2005. Other reports indicated a potential inflammatory component associated with brevetoxin exposure (Bossart et al, 1998;Walsh et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The purpose of this investigation was to evaluate the possible neurotoxic response associated with sub-acute inhalation of PbTx-3, one of the major brevetoxins produced by K. brevis. Inasmuch as the occurrence and distribution of K. brevis-induced red tide have increased over time, there may be increased risk from brevetoxin-induced toxic effects, especially among individuals working and living along beaches affected by red tides (Benson et al, 2005). We therefore examined the neurotoxic effects of subacute exposure of PbTx-3 via inhalation in a mouse model.…”
Section: Discussionmentioning
confidence: 99%
“…Kirkpatrick et al (2006) have reported increased frequency of emergency room visits for respiratory related illnesses, including pneumonia, during Florida red tide events. Brevetoxin-induced inhibition of antibody production has been found in rats (Benson et al, , 2005. In addition, Sayer et al (2005) reported DNA damage in human lymphocytes exposed to nanomolar concentrations of brevetoxins in vitro.…”
Section: Introductionmentioning
confidence: 96%
“…Brevetoxin-3 was chosen for these studies because it is a major component of brevetoxin-containing aerosols along red tide affected beaches . Further, it is a potent neurotoxin in vitro (Baden, 1989) and suppresses humoral immunity in rats following repeated inhalation (Benson et al, , 2005.…”
Section: Introductionmentioning
confidence: 99%